RUBY, a Putative Galactose Oxidase, Influences Pectin Properties and Promotes Cell-To-Cell Adhesion in the Seed Coat Epidermis of Arabidopsis. Issue 4 (8th March 2019) - Šola, Krešimir; Gilchrist, Erin J.; Ropartz, David; Wang, Lisa; Feussner, Ivo; Mansfield, Shawn D.; Ralet, Marie-Christine; Haughn, George W.
Abstract : A putative galactose oxidase, RUBY, promotes cell-to-cell adhesion between seed coat epidermal cells and modifies galactosylated RG-I pectin in the seed coat mucilage of Arabidopsis. Abstract: Cell-to-cell adhesion is essential for establishment of multicellularity. In plants, such adhesion is mediated through a middle lamella composed primarily of pectic polysaccharides. The molecular interactions that influence cell-to-cell adhesion are not fully understood. We have used Arabidopsis ( Arabidopsis thaliana ) seed coat mucilage as a model system to investigate interactions between cell wall carbohydrates. Using a forward-genetic approach, we have discovered a gene, RUBY PARTICLES IN MUCILAGE ( RUBY ), encoding a protein that is annotated as a member of the Auxiliary Activity 5 (AA5) family of Carbohydrate-Active Enzymes (Gal/glyoxal oxidases) and is secreted to the apoplast late in the differentiation of seed coat epidermal cells. We show that RUB Y is required for the Gal oxidase activity of intact seeds; the oxidation of Gal in side-chains of rhamnogalacturonan-I (RG-I) present in mucilage-modified2 ( mum2 ) mucilage, but not in wild-type mucilage; the retention of branched RG-I in the seed following extrusion; and the enhancement of cell-to-cell adhesion in the seed coat epidermis. These data support the hypothesis that RUBY is a Gal oxidase that strengthens pectin cohesion within the middle lamella, and possibly the mucilage of wild-type seed coat epidermal cells, through oxidation of RG-I Gal side-chains.